2022
DOI: 10.3389/fncel.2022.899484
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Inhibits Gasdermin D-Induced Pyroptosis via the PI3K/AKT/GSK3β Pathway to Attenuate Neuroinflammation in Early Brain Injury After Subarachnoid Hemorrhage in Rats

Abstract: Subarachnoid hemorrhage (SAH) is one kind of life-threatening stroke, which leads to severe brain damage. Pyroptosis plays a critical role in early brain injury (EBI) after SAH. Previous reports suggest that SAH-induced brain edema, cell apoptosis, and neuronal injury could be suppressed by dexmedetomidine (Dex). In this study, we used a rat model of SAH to investigate the effect of Dex on pyroptosis in EBI after SAH and to determine the mechanisms involved. Pyroptosis was found in microglia in EBI after SAH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…As indicated by our results, DEX decreased the levels of NLRP3, cleaved Caspase-1, GSDMD-N, IL-1β, and IL-18 in SK-N-SH cells. In agreement with our results, DEX inhibits lipopolysaccharide (LPS)-induced release of nuclear factor-kappaB and pro-inflammatory factors from BV2 microglia, thus ameliorating neuroinflammation (Bao et al, 2019), and DEX pretreatment ameliorates GSDMD-induced microglia pyroptosis via the PI3K/ AKT/GSK3β pathway in subarachnoid hemorrhage (Wei et al, 2022). Altogether, our findings initially demonstrated that DEX attenuates Ropi-induced neuronal pyroptosis to alleviate neurotoxicity.…”
Section: Discussionsupporting
confidence: 91%
“…As indicated by our results, DEX decreased the levels of NLRP3, cleaved Caspase-1, GSDMD-N, IL-1β, and IL-18 in SK-N-SH cells. In agreement with our results, DEX inhibits lipopolysaccharide (LPS)-induced release of nuclear factor-kappaB and pro-inflammatory factors from BV2 microglia, thus ameliorating neuroinflammation (Bao et al, 2019), and DEX pretreatment ameliorates GSDMD-induced microglia pyroptosis via the PI3K/ AKT/GSK3β pathway in subarachnoid hemorrhage (Wei et al, 2022). Altogether, our findings initially demonstrated that DEX attenuates Ropi-induced neuronal pyroptosis to alleviate neurotoxicity.…”
Section: Discussionsupporting
confidence: 91%
“…In the first 24 h after SAH, hyperactivated microglial and several brain blood immune cells (T cells, macrophages, and neutrophils) were significantly reduced by DEX, potentially providing neuroprotection for brain injury ( 290 , 320 ). DEX relieves microglial pyroction in post-SAH EBI by activating the PI3K/Akt/GSK3β pathway and inhibits SAH-induced release of pro-inflammatory cytokines ( 321 ). In terms of neuroprotection, this study also showed that DEX alleviated SAH-induced neuroinflammation in the context of the NLRP3 inflammasome and inhibited the TLR4/NF-κB pathway.…”
Section: Multiple Treatment Strategies For Sahmentioning
confidence: 99%
“…We verified the mechanical role of Dex in intracellular Akt, ERK, and NF-κB signaling in RA-FLSs [ 27 , 28 , 29 ]. We determined the levels of intracellular signaling proteins in multiple-input-stimulated RA-FLSs ( Figure 2 a–l).…”
Section: Resultsmentioning
confidence: 67%